Esthetic Interim Acrylic Resin Prosthesis Reinforced with Metal Casting - Verri, Fellippo Ramos [UNESP]; Pellizzer, Eduardo Piza [UNESP]; Mazaro, José Vitor Quinelli [UNESP]; de Almeida, Erika Oliveira [UNESP]; Falcon Antenucci, Rosse Mary [UNESP] (Wiley-Blackwell, 2009)
Fabrication of an interim prosthesis is an important procedure in oral rehabilitation because it aids in determining the esthetics, phonetics, and occlusal relationship of the definitive restoration. The typical material (acrylic resin) used in interim prostheses commonly fails due to fractures. During extended oral rehabilitation with fixed partial prostheses, high strength interim prostheses are often required to protect hard and soft tissues, avoid dental mobility, and to allow the clinician and patient a chance to evaluate cosmetics and function before the placement of the definitive prosthesis. Furthermore, a satisfactory interim prosthesis can serve as a template for the construction of the definitive prosthesis. The maintenance of this prosthesis is important during treatment for protection of teeth and occlusal stability. Procedures to reinforce interim prostheses help to improve performance and esthetics in long-term treatment. Due to the low durability of acrylic resin in long-term use, the use of reinforcing materials, such as metal castings or spot-welded stainless steel matrix bands, is indicated in cases of extensive restoration and long-term treatment. This paper describes an easy technique for fabricating a fixed interim prosthesis using acrylic resin and a cast metallic reinforcement.
Keywords: Prosthodontics; provisional; interim; temporary; prosthesis